2017
DOI: 10.1038/srep43478
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of haemoglobin and iron on in vitro mycobacterial growth inhibition assays

Abstract: The current vaccine against tuberculosis, live attenuated Mycobacterium bovis BCG, has variable efficacy, but development of an effective alternative is severely hampered by the lack of an immune correlate of protection. There has been a recent resurgence of interest in functional in vitro mycobacterial growth inhibition assays (MGIAs), which provide a measure of a range of different immune mechanisms and their interactions. We identified a positive correlation between mean corpuscular haemoglobin and in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 72 publications
(95 reference statements)
1
36
0
Order By: Relevance
“…Furthermore, we have identified an influence of hemoglobin (Hb) and iron on the direct MGIA (68). While variation in clinical parameters including Hb levels forms part of the overall picture for clinical cohort studies and whole blood is applicable in this context (29,69), it may confound measures of vaccine-induced control of mycobacterial growth and reduce sensitivity to detect a vaccine response (68).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have identified an influence of hemoglobin (Hb) and iron on the direct MGIA (68). While variation in clinical parameters including Hb levels forms part of the overall picture for clinical cohort studies and whole blood is applicable in this context (29,69), it may confound measures of vaccine-induced control of mycobacterial growth and reduce sensitivity to detect a vaccine response (68).…”
Section: Discussionmentioning
confidence: 99%
“…Using samples from the Oxford BCG vaccination study, a positive correlation was observed between mean corpuscular Hb levels and mycobacterial growth in the direct whole-blood MGIA ( 22 ). Experimental addition of Hb or ferric iron to PBMCs from both humans and nonhuman primates (NHPs) resulted in increased mycobacterial growth, an effect reversed by addition of the iron chelator deferoxamine.…”
Section: Immune Mechanisms Of Growth Inhibitionmentioning
confidence: 99%
“…Development and optimization of the MGIA assay as it is currently used have been recently reviewed at length (10,23). MGIA assays have been used already for cells of human (9, 12, 24-26), nonhuman primate (26), and mouse (11,13,14) origin.…”
Section: Introductionmentioning
confidence: 99%
“…BCG-vaccinated mice have reduced Mtb loads following infection compared with nonvaccinated animals, and this is paralleled by their splenocytes' capacity to reduce mycobacterial outgrowth in MGIA (11,13), supporting the assay's biological validity. BCG vaccination has mostly been used in such studies, because BCG affords at least partial protection against severe manifestations of TB disease, and efficiently induces IFN-γ-producing T cells (9,11,13,14,25,26). Although many researchers have attempted to identify the cellular subset(s) responsible for mycobacterial growth control, their identity remains inconclusive, and to some extent even elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation